Probing individual point defects in graphene via near-field Raman scattering. Issue 46 (5th November 2015) - Mignuzzi, Sandro; Kumar, Naresh; Brennan, Barry; Gilmore, Ian S.; Richards, David; Pollard, Andrew J.; Roy, Debdulal
Abstract : We demonstrate the capability of tip-enhanced Raman spectroscopy to probe individual point defects in graphene. Abstract : The Raman scattering D-peak in graphene is spatially localised in close proximity to defects. Here, we demonstrate the capability of tip-enhanced Raman spectroscopy (TERS) to probe individual point defects, even for a graphene layer with an extremely low defect density. This is of practical interest for future graphene electronic devices. The measured TERS spectra enable a direct determination of the average inter-defect distance within the graphene sheet. Analysis of the TERS enhancement factor of the graphene Raman peaks highlights the preferential enhancement and symmetry-dependent selectivity of the D-peak intensity caused by zero-dimensional Raman scatterers.